2018
DOI: 10.1103/physrevx.8.011035
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Topology of Density Matrices

Abstract: The mixedness of a quantum state is usually seen as an adversary to topological quantization of observables. For example, exact quantization of the charge transported in a so-called Thouless adiabatic pump is lifted at any finite temperature in symmetry-protected topological insulators. Here, we show that certain directly observable many-body correlators preserve the integrity of topological invariants for mixed Gaussian quantum states in one dimension. Our approach relies on the expectation value of the many-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
105
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 44 publications
(110 reference statements)
2
105
0
Order By: Relevance
“…In this section, we demonstrate that the robust spectral features of quadratic Lindbladians discussed in the main text are independent of properties of the steady state, the latter of which was the subject of study in Refs. [20][21][22][23]. Specifically, we show that any system with some topological features in its spectrum can be continuously deformed to a system with the same spectrum, but a trivial (infinite temperature) steady state, while at all times maintaining the relevant spectral gaps, symmetries, and locality of the equations of motion.…”
Section: Independence Of Spectral and Steady-state Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…In this section, we demonstrate that the robust spectral features of quadratic Lindbladians discussed in the main text are independent of properties of the steady state, the latter of which was the subject of study in Refs. [20][21][22][23]. Specifically, we show that any system with some topological features in its spectrum can be continuously deformed to a system with the same spectrum, but a trivial (infinite temperature) steady state, while at all times maintaining the relevant spectral gaps, symmetries, and locality of the equations of motion.…”
Section: Independence Of Spectral and Steady-state Propertiesmentioning
confidence: 89%
“…For example, these universal topological properties of the complex excitation spectrum -which have direct physical consequences in spectroscopy -are unconnected to the classification of steady-state density matrices employed in Refs. [20][21][22][23]. Our work highlights the various manifestations of band topology in a very general class of exactly solvable open systems, and provides formalisms which can be applied to understand generic interacting systems in future work.…”
mentioning
confidence: 93%
“…However, Eq. (36) implies that all eigenvalues of ρ −1H √ ρ are real. Thus, we reach a contradiction.…”
Section: Incompatibility and Dynamic Phase Of Mixed Quantum Statesmentioning
confidence: 99%
“…In a recent paper [18], it was shown that the winding of the many-body polarization introduced by Resta [27] upon a closed path in parameter space is an alternative and useful many-body topological invariant for Gaussian states of fermions. The polarization of a non-degenerate ground-state |ψ corresponding to a filled band of a lattice Hamiltonian with periodic boundary conditions is the phase (in units of 2π) induced by a momentum shift T P = 1 2π Im log ψ T ψ .…”
Section: Introductionmentioning
confidence: 99%
“…However, φ EGP remains well defined and meaningful for arbitrarily large but finite systems [18] as long as the so-called purity gap of ρ does not close. Furthermore as shown in [18] the EGP of a Gaussian density matrix is reduced to the ground-state Zak phase of a fictitious Hamiltonian in the thermodynamic limit L → ∞. The symmetries of this fictitious Hamiltonian determine the topological classification [12] following the scheme of Altland and Zirnbauer [33][34][35].…”
Section: Introductionmentioning
confidence: 99%